2018
DOI: 10.1186/s41938-018-0032-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trichoderma harzianum on tomato plant growth and its antagonistic activity against Phythium ultimum and Phytopthora capsici

Abstract: Effect of Trichoderma harzianum was investigated on plant growth and inhibitory activity against Phythium ultimum and Phytopthora capsici under laboratory and greenhouse conditions. Data under lab conditions revealed that mycelial growth of both pathogens were inhibited by T. harzianum in vitro. The effect of T. harzianum on different plant growth parameters was assessed in the presence of P. ultimum and P. capsici. Fresh and dry shoot weight was reduced by both fungal strains. The fresh shoot weight was decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…These fungi are known not only as biocontrol agents, but they also support plant growth and root development and induce plant defense mechanisms [47]. There are numerous reports in the literature about the beneficial effects of Trichoderma on tomato growth and yielding, for example Uddin et al [48] or Herrera-Téllez et al [49]. However, in the presented studies, no positive effect on the yield of tomato was found in the substrates highly colonized by these fungi (Table 10).…”
Section: Microbial Analyses Of Drainage Watersmentioning
confidence: 70%
“…These fungi are known not only as biocontrol agents, but they also support plant growth and root development and induce plant defense mechanisms [47]. There are numerous reports in the literature about the beneficial effects of Trichoderma on tomato growth and yielding, for example Uddin et al [48] or Herrera-Téllez et al [49]. However, in the presented studies, no positive effect on the yield of tomato was found in the substrates highly colonized by these fungi (Table 10).…”
Section: Microbial Analyses Of Drainage Watersmentioning
confidence: 70%
“…and T. harzianum led to an increase in root and shoot weight, in agreement with what was verified in the present study. In the same sense, Mwangi et al (2011) and Uddin et al (2018) reported that treatments with T. harzianum promoted the growth of tomato plants, even in the presence of pathogens.…”
Section: Effect Of Trichoderma Spp On the Hypocotyl Of Tomato Seedlingsmentioning
confidence: 81%
“…Moreover, previous studies have reported that Trichoderma spp. could promote the growth of bitter gourds, bottle gourds, cucumbers, peppers, rice, and tomato seedlings (Chagas et al, 2015;Kotasthane et al, 2015;Marin-Guirao et al, 2016;Herrera-Parra et al, 2017;Uddin et al, 2018). Additionally, Trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%